Bioethanol production using carbohydrate-rich microalgae biomass as feedstock - Ho, Shih-Hsin; Huang, Shu-Wen; Chen, Chun-Yen; Hasunuma, Tomohisa; Kondo, Akihiko; Chang, Jo-Shu (Bioresource technology, 2013)
► A sugar-rich Chlorella vulgaris FSP-E strain was used as feedstock for ethanol production. ► Enzymatic and acidic hydrolyses can efficiently saccharify the microalgae biomass. ► SHF & SSF processes produced ethanol from the microalgae biomass with high yield. ► SSF process gave better ethanol production performance with a 92% theoretical yield. This study aimed to evaluate the potential of using a carbohydrate-rich microalga Chlorella vulgaris FSP-E as feedstock for bioethanol production via various hydrolysis strategies and fermentation processes. Enzymatic hydrolysis of C. vulgaris FSP-E biomass (containing 51% carbohydrate per dry weight) gave a glucose yield of 90.4% (or 0.461g (gbiomass)−1). The SHF and SSF processes converted the enzymatic microalgae hydrolysate into ethanol with a 79.9% and 92.3% theoretical yield, respectively. Dilute acidic hydrolysis with 1% sulfuric acid was also very effective in saccharifying C. vulgaris FSP-E biomass, achieving a glucose yield of nearly 93.6% from the microalgal carbohydrates at a starting biomass concentration of 50gL−1. Using the acidic hydrolysate of C. vulgaris FSP-E biomass as feedstock, the SHF process produced ethanol at a concentration of 11.7gL−1 and an 87.6% theoretical yield. These findings indicate the feasibility of using carbohydrate-producing microalgae as feedstock for fermentative bioethanol production.